Dimensional Assessment of Psychopathy and Its Relationship with Physiological Responses to Empathic Images in Juvenile Offenders - Barros, Daniel M.; Dias, Alvaro M.; Serafim, Antonio; Castellana, Gustavo; Achá, Maria Fernanda; Busatto, Geraldo (Frontiers in Psychiatry, 2013)
Objective: Many psychophysiological studies investigate whether psychopaths present low levels of electrodermal activity (EDA). However, despite evidence that varying degrees of psychopathy are normally distributed in the population, there is a paucity of EDA studies evaluating dimensionally. Moreover, although lack of empathy is a cornerstone of psychopathy, there has been a lack of studies using pictures of empathic emotional content to assess psycophysiological responses. Method: We studied a population of young male delinquents (n=30) from a detention center, using the Psychopathy Checklist Revised (PCL-R) to determine if higher levels of psychopathy were related to lesser degrees of EDA in response to emotion-eliciting pictures of empathic content. Results: There were significant correlations (p